Pengaruh Kecerdasan Emosional terhadap Literasi Keuangan serta Implikasinya terhadap Perencanaan Keuangan Mahasiswa - Ayuningtyas, Dyah Melita Febryana; Gumilar, Gugum; Kurniawan, Kurniawan (Civiliza Publishing, Indonesia., 2023)
The rise of various symptoms of financial problems among students has serious impacts. Poor financial planning is indivisible from the impact of emotional intelligence and the level of money related proficiency. Financial planning must be managed properly and planned to achieve the desired life goals, so that financial planning can be said to be healthy. In this regard, a study investigating strategy was utilized with a quantitative approach, using Proportionate Stratified Random Sampling. From the results of the study it was found that there was a positive and significant influence between emotional intelligence on financial literacy, financial literacy on financial planning, and also emotional intelligence on financial planning. In addition, financial literacy is considered capable of mediating the impact of emotional intelligence on financial planning. And for the contribution of the indirect effect, which was 40%, it was greater than the direct effect, which was 28.6%. For further research, additional variables such as financial attitudes can be used, where this financial attitude is a person's discipline regarding how to manage finances which can later complement models that affect financial planning in expansion to the autonomous factors utilized in this way of thinking.